Faktor Faktor Yang Mempengaruhi Pedagang Muslim Melakukan Kredit Pada Peminjaman Modal Perorangan Di Kota Jambi: Studi Kasus Pasar Modern Handil - Susnaweli Susnaweli (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research was conducted to see whether there are factors that influence Muslim traders in providing credit to individual capital borrowers in Jambi City (handil capital market case study). Economic activity is one of the activities that is allowed to improve people's standard of living, especially traders. Trade is an activity carried out by people throughout the world, from trading in primary needs to luxury goods. Not only that, trading was also one of the business ventures carried out by the Prophet. From an economic perspective, the market is a place where sellers and buyers meet to determine an agreement on the price of exchanging goods or services. Markets are also social constructs because economic resources, namely goods and services, are allocated there. It is exchange and trading activities that build markets. In other words, there would be no trade without a market, and a market would not exist if there were no trade. The most basic thing in the trading process is social interaction. This interaction gives birth to norms and sanctions just like the beginning of the formation of society, where the role of all actors is very important. There will be no traders without buyers, and vice versa, and there will be no market without both parties. However, not only these two perpetrators, there are still other parties who are called loan sharks.